PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR PERTANAHAN KABUPATEN SIMALUNGUN - Saragih, Muhammad Arif; Lie, Darwin; Butarbutar, Marisi; Nainggolan, Lora Ekana (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2018)
The results of this study can be summarized as follows: 1. Motivation, job satisfaction and employee work discipline is good. 2. Regression analysis results are Å¶ = 17,600 + 1.086X1 + 1.028X2, meaning motivation and job satisfaction have a positive effect on employee work discipline. 3. Correlation analysis results obtained obtained value r = 0.883, meaning there is a high and positive correlation between motivation and job satisfaction with employee work discipline. The high level of work discipline can be explained by motivation and job satisfaction of 77.9%. 4. H0 Hypothesis rejected, meaning motivation and job satisfaction have a positive and significant effect on the work discipline of the Land Office employee of Simalungun Regency either simultaneously or partially.The suggestions of this research are: To increase the motivation of the leader should give confidence to the employees in completing the task given to him so that employees feel confident in working. To improve the job satisfaction of the leader should give attention, compensation, and career development well in accordance with the needs of the employee so that every job given the leadership can be done with a good attitude and satisfaction in the work continues to increase. To improve employee work discipline, agencies should act decisively in enforcing sanctions according to the rules that have been listed with the maximum and consistent, so that employees are aware and more disciplined themselves